Uji Beberapa Dosis Minyak Daun Kemangi Ocimum basilicum Linnaeus sebagai Atraktan terhadap Bactrocera spp. pada Tanaman Cabai - Fitriah Sucindra Mefta; Hafiz Fauzana (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2021)
Fruit flies, Bactrocera spp., are the primary pests on chili plants (Capsicum annuum Linnaeus). A safe and effective control uses traps combined with an attractant from basil leaf oil (Ocimum basilicum Linnaeus). This study aimed to determine the attractiveness of basil leaf oil against fruit flies at several different doses. This research was carried out in Organic Chemistry Laboratory STIFARM Padang, in Tabek Patah Tanah Datar area West Sumatra, and in the Pest Disease Observation and Development of Biological Agents Laboratory, Bukittinggi, West Sumatra, from June to August 2020. The treatment was in the form of different doses of basil leaf oil, which was 0,5 ml per trap, 1.0 ml per trap, 1.5 ml per trap, 2.0 ml per trap, and 2.5 ml per trap. The experiment used a completely randomized design with five treatments and three replications. This study found two species of fruit flies around chili plants, namely Bactrocera papayae and Bactrocera carambolae, which were dominated by male B. papayae. The traps containing 1.5 ml of basil leaf oil attracted the most fruit flies. Temperature and humidity significantly affect the abundance of individual fruit flies.